How does medicine ball pull over pass and resistance band training affect passing and shooting ability? A systematic review on the sport of handball - Haniyyah, Nida; Suhartini, Bernadeta; Salacup, Vince Louisse D. (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. The ability of an athlete to master passing and shooting skills is crucial for achieving success in handball. These fundamental techniques significantly influence a player's ability to contribute to their team's victory. Observations from the 2023 Pre-Province Championship revealed that poor passing and shooting skills negatively impacted gameplay, leading to unsuccessful scoring attempts and overall team performance. This study reviews literature on the effects of medicine ball pull-over pass and resistance band training on handball athletes' passing and shooting abilities.Material and Methods. A literature review was conducted using Scopus, ScienceDirect, and PubMed. Studies examining these training methods' effects on handball passing and shooting were selected following PRISMA guidelines. Inclusion criteria required experimental or quasi-experimental designs involving male or female handball athletes. Eight relevant studies were analyzed.Results. The results of the literature review showed that training with medicine ball pull over passes and resistance bands can generally improve physical ability, strength, and accuracy in passing and shooting in handball athletes. The studies analyzed indicated that resistance band training tended to provide more significant improvements in core muscle strength and stability, which contributed to improved passing and shooting performance. Meanwhile, medicine ball pulls over pass training is also effective in improving muscle strength and coordination, but with more variable impacts depending on the intensity and duration of training.Conclusions. Both methods effectively enhance passing and shooting, with resistance band training providing more consistent benefits in core strength and stability. Future studies should explore long-term effects, optimal protocols, and training combinations to maximize performance.